Effect of atorvastatin on cellular adhesion molecules on leukocytes in patients with normocholesterolemic coronary artery disease - Walter, Thomas; Süselbeck, Tim; Borggrefe, Martin; Swoboda, Stefanie; Hoffmeister, Hans Martin; Dempfle, Carl-Erik (In vivo, 2010)
Expression of cellular adhesion molecules on leukocytes plays a key role in coronary artery disease (CAD). The aim of the present study was to assess whether atorvastatin therapy has an impact on the expression of cellular adhesion molecules on leukocytes in patients with normocholesterolemic CAD.
Gesehen am 04.10.2023
Kein DOI vorhanden